PERBEDAAN PENGGUNAAN VARIASI MERK BAHAN BAKAR GASOLINE PADA MESIN 1NR-VE NORMALLY ASPIRATED TERHADAP EMISI GAS BUANG - Supiyadi, Ahmad; Retno Eka Pramitasari; Dian Anisa Rokhmah Wati; Basuki (UNHASY, 2025)
His research is motivated by researchers who are interested in testing Pertamax, Shell Super, and Mobil fuels by comparing the differences in exhaust emissions. The purpose of this study is to determine the exhaust emissions of Pertamax, Shell Super, and Mobil fuels.This study uses an experimental method with testing variations of 3 fuels. This test was carried out with several variations of rpm. This test uses an exhaust gas analyzer on a 1NR-VE engine. For the rpm variations used, the rpm is 800 to 4000 with a difference of 200 in each rpm. The data results are processed using a table and described using a diagram to determine the exhaust gas graph produced by the engine.The results of the study showed that there was a difference in the test results with the test results using Pertamax fuel showing the best HC value at rpm 2800 with an HC value of 0 Ppm and with a CO₂ gas value of 12%. While for the HC gas value in Shell Super fuel, the best is at rpm 2000, 2600, 2800, and rpm 3400 with a value of 0 Ppm and CO₂ gas of 11.90% and for Car fuel, the test results with the best HC gas value at rpm 2600 with a value of 0 Ppm and CO₂ gas of 11.90%.